A Novel Condition to the Harmonic of the Velocity Vector Field of a Curve in Rn - Ayşe Altın; Canan Köroğlu (Discrete Dynamics in Nature and Society)
In this paper, a condition is obtained for the harmonic of the velocity vector field in the curve family passing through the fixed p and q points in Rn. It shows that the condition can be expressed in terms of the curvature functions. Finally, we give an example which provides the mentioned condition in this work and illustrates it with figures.